Pancytopenia as the initial presenting feature in multiple myeloma: a case series - Roy, Somnath S.; Saha, Aritra; Pegu, Ajit K.; Islam, Navil F.; Ozah, Jinku; Rahman , Sofiur (International Journal of Advances in Medicine, 2023)
Multiple myeloma is a plasma cell neoplasm characterized by abnormal proliferation of clonal cells in the bone marrow. Anaemia is generally the most common feature from hematologic aspect and bone pain being the other important symptom, but pancytopenia as the presenting feature is unusual. Here, we shared our experience of 3 cases with non-specific symptoms with pancytopenia which on through evaluation revealed our diagnosis. A hospital based observational descriptive case series was conducted wherein all the cases of multiple myeloma presenting with pancytopenia were included. Complete blood picture, peripheral smear, bone marrow aspirate and serum protein electrophoresis were reviewed and analysed. Pancytopenia as the initial presenting feature of multiple myeloma is an unique manifestation and diagnosing such cases require high degree of suspicion to avoid delay in the initiation of treatment.